A Study on the Presence of Pathogenic Leptospira spp. in Environmental Water Samples Obtained from Selected Recreational Areas in Terengganu, Malaysia - Salwani, Ismail; Nor Iza, A.Rahman; Noor Zarina, Abd Wahab (2014)
Leptospirosis is a zoonosis of worldwide distribution. It is endemic in Malaysia and is caused by infection with pathogenic Leptospira species. Leptospires can survive in water for many months hence water is an important vehicle in their transmission. Recreational activities such as swimming, fishing, canoeing and rafting place a person at risk for the infection. The objective of this study was to detect the presence of pathogenic Leptospira spp. in environmental water samples obtained from selected recreational areas in Terengganu. A total of 40 water samples (2000 ml) were collected from two recreational areas in north Terengganu namely Lata Tembakah and Lata Belatan Waterfalls. The samples were inoculated into modified semisolid Ellinghausen McCullough Johnson Harris (EMJH) media, incubated at 30°C for one month and examined under the dark-field microscope. Positive growth for the pathogenic leptospires was then confirmed by Polymerase Chain Reaction (PCR) assay using G1/G2 primers. Pathogenic leptospires were detected in both recreational areas, 5% (1 out of 20) samples and 10% (2 out of 20) samples from Lata Tembakah Waterfall and Lata Belatan Waterfall respectively and were confirmed positive for the presence of pathogenic leptospires. As a conclusion, pathogenic leptospires were detected at two recreational areas in Terengganu and this would pose a risk of infection to human and lead to leptospirosis outbreak. Therefore, based on the result of this study, precautionary steps should be taken by responsible authorities to prevent human infection or leptospirosis outbreak.